KONTRIBUSI IDENTITAS MEREK, KUALITAS LAYANAN, DAN STANDAR HARGA DALAM MENENTUKAN PEMBELIAN TIKET LION AIR DI YOGYAKARTA - Hartini Prasetyo Wulandari; Asih Endah Subandiyah (Journal Competency of Business, 2026)
Study This aim For analyze contribution identity brand , quality service and standards price to decision purchase Lion Air tickets in Yogyakarta. This study important Because industry flight cost low the more competitive , while consumer No only consider price tickets , but also image brand , experience service , transparency costs , and suitability accepted values . The Yogyakarta context becomes relevant because Yogyakarta International Airport or YIA is one of the knot mobility air important in the southern region of Java, with Then cross continued flights and passengers​ recorded by the Directorate General Air Transportation . Lion Air also expanded service from Yogyakarta, one of them through Yogyakarta-Tarakan route in 2025. Research This use approach quantitative with method survey to consumers who have ever buy or use Lion Air tickets from or towards Yogyakarta. The sample was determined with purposive sampling technique . Data were analyzed use multiple linear regression or Partial Least Square Structural Equation Modeling . Research results expected show that identity brand , quality service and standards price own influence positive to decision purchase ticket . Findings This can give input for management airline in strengthen trust consumer through consistency identity brand , improvement quality services , as well as policy transparent and competitive prices .​